Pro-Environmental Behaviour of Two Norway's Mainstream Mass Media - Fauzi, Mohammad Farras; Nugrahani, Henny Saptatia Drajati (Journal of Strategic and Global Studies, 2024)
This research aims to analyze the critiques of mainstream mass media in Norway in response to the plastic waste issue in the Nordic region based on pro-environmental behaviour.. The study will also examine the constraints or challenges faced by mass media in Norway in their agenda to combat plastic waste. In this process, the research will identify the strengths and weaknesses of mass media in shaping perceptions and driving positive actions in plastic waste management. The study will also analyze how mass media engages stakeholders, including the government, non-governmental organizations, and industry, in efforts to combat plastic waste in Norway. This research will identify strategies, collaborations, and interactions between mass media and these stakeholders. The goal is to assess the extent to which mass media can engage and coordinate joint efforts with other stakeholders. Mass media in Norway can have a stronger role in influencing government policies related to plastic waste and often urge the government to implement more sustainable measures in plastic waste management. Mass media in Norway can also act as a powerful information disseminator in addressing the urgency of plastic waste management to the public.